Práticas docentes para atuação na educação do campo - LOBATO, Ana Lúcia Vasconcelos (2019)
The purpose of this article is to analyze how training and teaching practices are to be used in rural education. The objective is to analyze how the teaching practices of educators working in rural schools are taking place, as well as to conceptualize, historically and socially, the genesis of rural education and rural schools in Brazil. We will then try to argue the theoretical and practical bases that support the reflections about the teacher formation to act in the field as precursor of the development of cognitive abilities in its school space. We organize this article in three topics where we aim to refer through a historical and legal analysis to the process of training these professionals, reflecting on the role of the education professional of the field, we will also try to reflect how this education professional has been working in this process and what your academic background to give you with the new. The present research article establishes the longitudinal temporal sequence. It is to define the Universe of the study population of the basic education and to define the Sample as part that will represent the Universe that will be the four Professors of a rural community of the municipality of Abaetetuba / PA, known as Jarumã the Municipal School Adriano Rodrigues Cardoso where we found accessibility and typicity for constituted research, and the conclusion by means of the analysis of data collected in loco and conclusive arguments based on the results of the questionnaires used with the teachers used in the research and thus we exposed our perceptions elaborated from the methodological walk we experienced in the the present work. This research had the theoretical basis of several authors that permeate the discussions on the subject.